2011
DOI: 10.1007/s12149-011-0546-3
|View full text |Cite
|
Sign up to set email alerts
|

The agreement of left ventricular function parameters between 99mTc-tetrofosmin gated myocardial SPECT and gated myocardial MRI

Abstract: In quantifying of left ventricular function parameter, gated CMR provides similar quantitative values comparing with gated MPS except for ventricular volumes in rest conditions. In contrast, there were certain variations except for LVEF in exercised examinations. When we follow patients by the same cardiac parameters with CMR and MPS, using parameters across the two modalities proved to be possible under rest condition. However, it is limited at exercise condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…In contrast, a substantial bias was found in the measurement of ventricular volumes. This result is consistent with previous studies that compared QGS analysis with cardiac MR, reporting an underestimation of ventricular volumes even with 16-frame gating (29,34,35). Our results showed that this underestimation persists with CZT SPECT cameras, despite a higher spatial resolution.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, a substantial bias was found in the measurement of ventricular volumes. This result is consistent with previous studies that compared QGS analysis with cardiac MR, reporting an underestimation of ventricular volumes even with 16-frame gating (29,34,35). Our results showed that this underestimation persists with CZT SPECT cameras, despite a higher spatial resolution.…”
Section: Discussionsupporting
confidence: 93%
“…Due to the inferior temporal resolution of CCTA to 2DE, the peak velocity, E/A, and E/E' may have been underestimated. This limitation may be overcome by increasing the sampling rate or reducing the heart rate, if medically possible (10,14,29). Second, we applied simple exclusion criteria for selecting the study population, which consisted of patients who underwent cardiac surgery or coronary intervention.…”
Section: Discussionmentioning
confidence: 99%
“…When 16-frame gating is used, normal limits for PFR and time to PFR are similar to those reported with gated blood-pool studies. Agreement between SPECT and MRI in both PFR and time to PFR has been demonstrated when 32-frame gating is used for SPECT (48). Global time to PFR was shown to be less sensitive than regional parameters (49).…”
Section: Global LV Functionmentioning
confidence: 95%